The Twenty-First Century Conflicts - Marsili, M. (Encontro Anual da Investigação & Desenvolvimento em Ciências Militares 2018 (EAI&DCM 2018):, 2018)
Alongside non-international and international conflict, a third category of armed conflict is emerging: hybrid, asymmetric, and transnational conflict which involve state and non-state actors such as insurgents or terrorist organizations. Unconventional conflicts are among the trend topics of defense and security, and they pose a threat to the stability of international order. States and international organizations, such as the UN and NATO, face difficulty using legal tools currently provided by international law, in particular international humanitarian law (IHL) and the law of war (Geneva and Hague conventions). The issue is how current international law applies or can be adapted to these conflicts. There are some questions to be fixed. First, we should find whether new rules are required to deal with situations of hybrid conflict, or if current rules are still valid and can be used/adapted. Secondly, we should determine whether IHL applies in transnational armed conflict against non-state groups, and if their members cease to be targetable during a pause in their active involvement, and whether there can be a non-international armed conflict which has no finite territorial boundaries with a non-state armed group operating transnationally. Lastly, we should assess whether attacks carried out by a transnational organisation and its affiliates meet the criteria of qualifying as a state of armed conflict under IHL.